answersLogoWhite

0


Best Answer

9c is.

User Avatar

Wiki User

โˆ™ 2013-02-05 19:31:49
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar

Add your answer:

Earn +20 pts
Q: What is 3c plus 5c plus c simplified?
Write your answer...
Submit
Still have questions?
magnify glass
imp
Related questions

What is the like term for 5c plus 2c plus 4b plus 3c?

The like terms are sums of b terms and c terms separately 5c+2c+3c+4b 5c +2c + 4b + 3c => 10c + 4b


Factor of 5C2 plus 3C-2?

(5c - 2)(c +1)


What is the answer of 5c plus 4b - c - 2b?

The simplified answer is: 4c+2b


12 equals 3c-12 plus 5c what is C?

3c - 12 + 5c = 12Combine the 'c' terms on the left side:8c - 12 = 12Add 12 to each side:8c = 24Divide each side by 8:c = 3


3c plus 15 over c squared minus 5 plus c over c plus 5?

(3c +15)/(c2 - 5) + c/(c + 5)= (3c + 15)/(c - 5)(c + 5) + c/(c + 5)= (3c + 15)/(c - 5)(c + 5) + [c(c - 5)/(c + 5)(c - 5)(since the common denominator is (c + 5)(c - 5)= (3c + 15)/(c - 5)(c + 5) + (c2 - 5c)/(c + 5)(c - 5)= (3c + 15 + c2 - 5c)/(c - 5)(c + 5)= (c2 - 2c + 15)/(c - 5)(c + 5)= [(c - 5)(c + 3)]/(c - 5)(c + 5) (simplify)= (c + 3)/(c + 5)


What is the answer to 20c plus 5 equals 5c plus 65?

20c + 5 = 5c + 65 Divide through by 5: 4c + 1 = c + 13 Subtract c from both sides: 3c + 1 = 13 Subtract 1 from both sides: 3c = 12 Divide both sides by 3: c = 4 20c + 5 = 5c +65 20c - 5c= 65 - 5 15c = 60 15c/15 = 60/15 c = 4 (alternative method)


3c-12 equals 14 plus 5c?

3c - 12 = 14 + 5cSubtract 3c from each side:-12 = 14 + 2cSubtract 14 from each side:-26 = 2cDivide each side by 2:-13 = c


What is c plus C plus C answer in algebra?

3c


How do you factor c square plus 5c plus 6?

c2 + 5c + 6 = (c + 2)*(c + 3)


What is c plus 2c plus 3c?

6c.


B plus b plus c plus c plus c plus c equals?

2b+3c


What is 4a plus 3c-2b-c plus a-b?

4a + 3c - 2b - c + a - b = 5a - 3b + 2c


What temp in Fahrenheit reads three times that in celsius?

80°F = 262/3°C To convert Celsius to Fahrenheit, the formula is F = 9/5C + 32. If the Fahrenheit reading is 3 times the Celsius reading then F = 3C, so 3C = 9/5C + 32 : 6/5C = 32 : C = 262/3. Then F = 3C = 3 x 262/3 = 80


How do you do 4c plus 2 equals 3c plus 9?

4c+2 = 3c+9 4c-3c = 9-2 c = 7


Is c plus c plus c equals 6 isolated?

If: 3c = 6Then: c = 2


Find the illegal values of c in the multiplication statement c2-3c-10 over c2 plus 5c-14 by c2-c-2 over c2-2c-15?

c=-7,c=-3,c=2,c=5


What is 2c plus 4-3c equals -9 plus c plus 5?

2c + 4 - 3c = -9 + c + 5 -c + 4 = c - 4 -2c = -8 2c = 8 c = 4


4 plus 3c equals 2 c plus 2 what does c equal?

4 + 3c = 2c + 2Subtract 4 from each side:3c = 2c - 2Subtract 2c from each side:c = -2


How do you simplify 4c2 plus 5c plus 2c?

4c2 + 5c + 2c = 4c2 + 7c = c(4c + 7)


What is 3c plus 6 equals 18?

3c+6=18 3c+6-6=18-6 3c=12 3c÷3=12÷3 c=4


17 - 3c equals 4c plus 3?

17-3= 4c+3c c=2


What is -5c plus 9 and how?

You can't tell a thing about -5c+9 until you know what 'c' is. And every time 'c' changes, -5c+9 changes.


C-6 C plus 7?

C - 6C + 7 = -5C + 7


What is 3a plus ab plus 3c plus bc?

That factors to (b + 3)(a + c)


How do you factor c cubed plus 27?

(c + 3)(c^2 - 3c + 9)